2021
DOI: 10.3389/fneur.2021.704788
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Maximal Tongue Pressure and Swallowing Function in Spinal and Bulbar Muscular Atrophy

Abstract: Background: Spinal and bulbar muscular atrophy (SBMA) is an X-lined motor neuron disease characterized by progressive muscle weakness, bulbar palsy, and dysphagia. Dysphagia is associated with tongue weakness, which is a common manifestation of SBMA. This study aimed to investigate the correlations between tongue pressure and dysphagia in patients with SBMA.Materials and Methods: Thirty-nine genetically confirmed SBMA patients underwent a videofluoroscopic swallowing study (VFSS) and tongue pressure assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Notably, painful abdominal cramps seemed to be specific to HMSN-P. Painful abdominal cramps have not described in related diseases, e.g., ALS, spinal bulbar muscular atrophy (SBMA), or Charcot-Marie-Tooth (CMT) disease (10)(11)(12)(13). Fasciculation in the face during tongue thrust has been observed in ALS and SBMA patients but not HMSN-P, and CMT disease shows findings of lower-extremity predominance.…”
Section: Resultsmentioning
confidence: 94%
“…Notably, painful abdominal cramps seemed to be specific to HMSN-P. Painful abdominal cramps have not described in related diseases, e.g., ALS, spinal bulbar muscular atrophy (SBMA), or Charcot-Marie-Tooth (CMT) disease (10)(11)(12)(13). Fasciculation in the face during tongue thrust has been observed in ALS and SBMA patients but not HMSN-P, and CMT disease shows findings of lower-extremity predominance.…”
Section: Resultsmentioning
confidence: 94%
“…Measurements during functional activities such as swallowing are also demanding because the procedure of swallowing itself is very complex, consists of different steps [33], and depends on parameters such as the type of device used [35], the type of bolus [36], the amount of occlusal units [35], etc. Maximum tongue pressure is a simpler measurement to take, is less dependent on other external factors, can be compared between studies and/or patients, is correlated with the swallowing function [35], and has been used as a diagnostic feature to detect muscular diseases [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Impairment of the tongue seems to represent a major risk factor for aspiration [18]. One study showed a correlation between tongue pressure and the severity of dysphagia and physical performance in 39 patients with ALS [19]. Although swallowing pressures are known to be considerably weaker than maximum pressure exerted by tongue-palate contact pressure tasks, specific measures of maximum tongue strength have been shown to be associated with overall swallowing performance [20].…”
Section: Physiopathology Of Dysphagia: Focusing On Alsmentioning
confidence: 99%